PENGARUH DEBT TO EQUITY RATIO, PROFITABILITAS, KEPEMILIKAN PIHAK LUAR, KUALITAS AUDITOR, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN FOOD AND BAVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2013 - Urvan Maulana Ubah; Zulbahridar -; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to analyze the influence of debt to equity ratio, profitability, outsider ownership, reputation of public accountant, and firms size to timeliness of financial reporting of the food and baverages firm listed in Indonesia Stock Exchange. The samples consist of 13 food and baverages firms listed in Indonesian Stock Exchange (IDX) and sent the report on finance to Bapepam in the period years 2010-2013. The data that was used in this research was the secondary data and selected by using purposive sampling method. The analyzed method used in this research is multiple regression analysis by using SPSS (Statistical Product and Service Solution) 20. The result of this research provides evidence that debt to equity ratio, profitability, reputation of public accountant, and firms size have influence to timeliness of financial statement forwarding. However there is no evidence that outsider ownership have influence on timeliness of financial statement forwarding.Keywords: timeliness, debt to equity ratio , profitability, reputation of public accountant, and firms size.